A Guide to Investor Targeting in Agribusiness - World Bank Group (Washington, DC, 2015)
This toolkit serves as a guide to help project leaders in working with client governments to attract concrete agribusiness investments that create jobs, reduce poverty, and develop value chains in an environmentally and socially sustainable way. However, the toolkit can be used by anyone working to attract sustainable private investment to a developing a country s agribusiness sector. These may be public officials, development organization staff, or consultants working in investment promotion, industrial development, or general economic development. Borrowing heavily from lessons learned in Bank Group projects, this toolkit helps project leaders to develop and execute actual targeting campaigns, by providing a step-by-step guide and, through the appendices, practical tools for implementation. The tools are in the form of templates, research resources, and examples of materials for investors. The toolkit is divided into four chapters corresponding to four essential steps in the targeting process. They are: step 1) understanding the context for a sector targeting campaign (also known as scoping); step 2) identifying competitive subsectors that might be best placed to attract new investments (also known as a sector scan); step 3) planning a targeting campaign aimed at the selected subsectors; and step 4) executing a targeting campaign and following up. This toolkit is designed in a way to take the reader directly to one of thirty four appendices.